A chromosome-scale genome assembly of Giardia duodenalis by long-read sequencing of ten trophozoites - Jingjing Sun; Yuancai Chen; Yizhuo Wei; Kaihui Zhang; Yin Fu; Zi Yan; Xingyu Zhu; Sumei Zhang; Longxian Zhang; Junqiang Li (Scientific Data)
Abstract Giardia duodenalis, a protozoan parasite of important zoonotic concern, is estimated to cause approximately 280 million human infections annually worldwide. Currently, genome sequencing of G. duodenalis mainly relies on in vitro axenic clones; however, for non-culturable or hard-to-cultivate microorganisms, obtaining sufficient DNA for whole-genome sequencing poses a great challenge. In this study, we isolated ten G. duodenalis trophozoites using single-cell selection technology, followed by the extraction of whole-genome DNA and its amplification via multiple displacement amplification (MDA). The G. duodenalis DNA was sequenced by long-read sequencing (Oxford Nanopore Technologies and Pacific Biosciences), and three main assembly tools (Canu, MECAT2, and RagTag) were used to assemble the sequenced data. As a result, a chromosome-scale genome of G. duodenalis was successfully assembled (assemblage A1 isolate g12a2), with a total genome size of 11.1 Mbp, five contigs, and an N50 value of 3.1 Mbp. This study achieved a chromosome-scale G. duodenalis genome sequencing and assembly from groups of 10 trophozoites, which facilitates protozoan single cell genomics research.